System Identification of Tunnel Response to Ground Motion Considering a Simplified Model - Alonso-Rodriguez, Andres; Nikitas, Nikolaos; Knappett, Jonathan; Kampas, Georgios; Anastasopoulos, Ioannis; Fuentes, Raul (Frontiers in Built Environment, 2018)
This paper presents a simplified model using coupled Bernoulli and shear beams supported by Winkler-type springs for system identification of tunnels subjected to earthquake-induced ground motions. The model formulation is introduced and closed-form solutions to the modal characteristic equation and mode shapes are derived. The latter are verified against the results of numerical models. Then, the system identification algorithm is presented, showcasing its ability to recover model parameters when recorded acceleration time histories along the tunnel are compromised by noise and sensor locations are varied. The presented framework can be used to initially and, simply, recover tunnel response when monitoring data is available, or to plan for monitoring campaigns in newly constructed or existing tunnels.